Towards a psychophysics of interoceptive processes: the measurement of heartbeat detection - Brener, Jasper; Ring, Christopher (Philosophical transactions of the Royal Society of London. Series B. Biological sciences, 2016)
It is difficult to collect objective evidence of interoception. Unlike exteroception, the effective stimuli for interoception are often unknown, and even when identifiable, they are difficult to control experimentally. Furthermore, direct stimulation of the interoceptors is seldom appropriate in human experimentation. Hence, non-invasive behavioural measures of accuracy in heartbeat detection have frequently been adopted to index interoceptive sensitivity. However, there has been little standardization and the two most popular methods for assessing heartbeat detection, heartbeat tracking and two alternative forced choice methods, appear to be biased and of questionable validity. These issues do not arise with other methods that are based on classical psychophysics and that enable subjects to indicate when during the cardiac cycle their heartbeat sensations occur. Not only are these classical methods highly reliable, but they also provide continuous unbiased measures of the temporal locations of heartbeat sensations and the precision with which these sensations are detected. This article is part of the themed issue ‘Interoception beyond homeostasis: affect, cognition and mental health’.